PERFORMANCE OF GILLNET-MESH SIZE SELECTIVITY FOR THREE FLYINGFISH SPECIES IN AMBON WATERS, MOLUCCAS PROVINCE - Hutubessy, Barbara Grace; Syahilatua, Augy (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
The gillnets' performance for capturing flying fish was obtained from the selectivity parameters of each mesh size. Gillnet selectivity parameters for flying fish were estimated using multi-panel drift gillnets with four different mesh sizes in southern Ambon Island. The black-spot flying fish Cheilopogon suttoni reached peak selectivity at 20.34 cm for mesh size of 1.25